Music in America's Cold War Diplomacy - Fosler-Lussier, Danielle, 1969- (Book collections on Project MUSE., 2015)
"During the Cold War, thousands of musicians from the United States traveled the world under the sponsorship of the U.S. State Department's Cultural Presentations program. Using archival documents and newly collected oral histories, this study illuminates the reception of these musical events, for the practice of musical diplomacy on the ground sometimes differed substantially from what the department's planners envisioned. Performances of music in many styles--classical, rock 'n' roll, folk, blues, and jazz--were meant to compete with traveling Soviet and Chinese artists, enhancing the reputation of American culture. These concerts offered large audiences evidence of America's improving race relations, excellent musicianship, and generosity toward other peoples. Most important, these performances also built meaningful connections with people in other lands. Through personal contacts and the media, musical diplomacy created subtle musical, social, and political relationships on a global scale. Although these tours were sometimes conceived as propaganda ventures, their most important function was the building of imagined and real relationships, which constitute the essence of soft power"--Provided by publisher.